The ecological crisis and post-Keynesian economics – bridging the gap? - Vera Huwe; Miriam Rehm (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2022)
This paper investigates whether post-Keynesian economics is well-equipped to address the ecological crisis we face today. The major crisis of our times has three interrelated dimensions: ecological overshoot, socio-economic inequality and a growth imperative built into the economic system. We argue that the main building blocks of post-Keynesian thought – in contrast to neoclassical approaches – are well-placed for addressing the ecological crisis if reconfigured accordingly, and that such a development will likely be very fruitful. Yet, we identify the growth effects of reducing inequality, the capitalist growth imperative and political power from wealth concentration and incumbent industries as the main contradictions between post-Keynesian theory and fossil phase-out. While the first of these may be overcome with adequate industrial and regulatory policy, the second would require a fundamental transformation. This, in turn, is impeded by the third. We argue that more attention should be paid to resolving the residual contradictions and indicate advances in the broader Political Economy and Ecological Economics literature that may serve as a starting point, in particular focusing on human needs.
Keywords: 330; post-Keynesian economics; ecological economics; crisis; inequality; ecology; growthE12; Q52; B51; D31; D21